Best Practice for Transitioning from Carbon Dioxide (CO2) Enhanced Oil Recovery EOR to CO2 Storage. (July 2017) - Allinson, Ken; Burt, Dan; Campbell, Lisa; Constable, Lisa; Crombie, Mark; Lee, Arthur; Lima, Vinicius; Lloyd, Tim; Solsbey, Lee
Abstract: The purpose of Carbon Capture and Storage (CCS) is to reduce emissions of greenhouse gases to the atmosphere as a climate change mitigation activity. However, given the relatively high costs currently associated with CCS, coupling CCS with Enhanced Oil Recovery (EOR) could provide a critical financial incentive to facilitate development of CCS projects in the near term. One issue is that projects to enhance oil production are primarily implemented to increase oil production with (tertiary recovery methods and any long term storage of CO2 is considered a potential ancillary benefit. When projects are designed as CCS from the start, there is typically a site evaluation process to review the storage formation according to best practice criteria for CCS. In EOR, the formation where CO2 would be stored is predetermined by the existing oil bearing reservoir, raising potential questions about monitoring, long-term CO2 storage liabilities, potential, leakage, permanence and other issues that must be addressed in CCS projects but may fall outside the boundaries of a typical EOR project. Finally, although this paper is premised on historical and current experiences with enhanced oil recovery projects, similar considerations could also be given to enhanced recovery of natural gas. There are no specific technological barriers or challenges in transitioning and converting a pure CO2 -EOR operation into a CO2 storage operation but there are a number of legal, regulatory and economic differences which must be addressed if an EOR project is to serve as a CCS project. Lack of experience or unresolved issues related to EOR becoming CCS could create barriers unless the issues are fully understood and managed to the satisfaction of regulators. Understanding best practice and the policy and regulatory frameworks affecting CCS from EOR is an important driver for ensuring that CO2 -EOR projects are developed in a manner which will enable the carbon stored to be recognised as a mitigation activity under local legislation/carbon market schemes and in national GHG inventories which support monitoring progress under the COP21 Paris Agreement. The paper provides an overview of the key issues in the USA, Canada, EU, Australia, and Brazil and provides recommendations for what companies need to do should they wish to transition from EOR to CCS for existing or future operations.